2014
DOI: 10.1038/cdd.2014.82
|View full text |Cite
|
Sign up to set email alerts
|

DLX3 regulates bone mass by targeting genes supporting osteoblast differentiation and mineral homeostasis in vivo

Abstract: Human mutations and in vitro studies indicate that DLX3 has a crucial function in bone development, however, the in vivo role of DLX3 in endochondral ossification has not been established. Here, we identify DLX3 as a central attenuator of adult bone mass in the appendicular skeleton. Dynamic bone formation, histologic and micro-computed tomography analyses demonstrate that in vivo DLX3 conditional loss of function in mesenchymal cells (Prx1-Cre) and osteoblasts (OCN-Cre) results in increased bone mass accrual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
38
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 49 publications
1
38
0
Order By: Relevance
“…A variety of human, mouse and fish studies suggest reduced expression of Grhl3, Dlx3, Dlx5 and Osx1 could explain the defects we found in calcium and phosphate metabolism (Dworkin et al, 2014;Han et al, 2011;Isaac et al, 2014;Lapunzina et al, 2010;Liu et al, 2015;Nguyen et al, 2013;Ting et al, 2003a). Mineralization of the endochondral skeleton is a complex biological process involving the formation of a calcium phosphate hydroxyapatite crystal that is deposited into an organic extracellular matrix composed primarily of type I collagen.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of human, mouse and fish studies suggest reduced expression of Grhl3, Dlx3, Dlx5 and Osx1 could explain the defects we found in calcium and phosphate metabolism (Dworkin et al, 2014;Han et al, 2011;Isaac et al, 2014;Lapunzina et al, 2010;Liu et al, 2015;Nguyen et al, 2013;Ting et al, 2003a). Mineralization of the endochondral skeleton is a complex biological process involving the formation of a calcium phosphate hydroxyapatite crystal that is deposited into an organic extracellular matrix composed primarily of type I collagen.…”
Section: Discussionmentioning
confidence: 99%
“…Dlx3 is a member of the distalless homeobox family that interacts with transcription factors specific to mineralized tissue to regulate craniofacial and postnatal skeletal development (33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). Our results indicate that there is a cellular requirement for miR-665 to fine-tune the expression of Dlx3 within physiologic limits for maturation of progenitors to odontoblasts.…”
Section: Discussionmentioning
confidence: 75%
“…Mutations in DLX3 in humans have been associated with tricho-dento-osseous syndrome (TDO; OMIM 190320) and amelogenesis imperfecta with taurodontism (AIHHT; OMIM 104510), both of which are conditions characterized by abnormalities in tooth formation (35-39). During development, Dlx3 expression occurs in cranial neural crest cells, endochondral osteoblasts, odontoblasts, ameloblasts, hypertrophic chondrocytes, and the developing limb (40,41), and Dlx3-knockout mice die from placental failure at embryonic day 9.5 (E9.5), prior to bone and tooth formation (28). Expression of DLX3 in postmigratory neural crest cells (E9.5) helps commit these cells to further differentiate into odontoblasts and cementoblasts, contributing to formation of mature dentin and cementum for proper tooth formation (40).…”
mentioning
confidence: 99%
“…In this issue of Cell Death Differentiation, Isaac et al 15 perform the first in vivo study of the postnatal role of DLX3 in the appendicular skeleton. They generate and analyse mice carrying conditional loss-of-function mutations of Dlx3 in mesenchymal cells (Dlx3 Prx1-cKO ) or in osteogenic lineage cells (Dlx3 OCN-cKO ).…”
mentioning
confidence: 99%
“…In vitro studies have shown that Dlx3 and Dlx5 associate with the Ocn promoter at the onset of transcriptional activation, concomitant with Runx2 occupancy, and, while Dlx3 occupancy on the Ocn promoter decreases from osteoblast maturation to mineralization, Dlx5 occupancy is maximal during the mineralization stage. 12 Isaac et al 15 demonstrate that Dlx3 deletion in calvaria osteoblasts results in increased occupancy of Dlx5 and increased and premature occupancy of Runx2 on regulatory elements on the Ocn promoter. Thus, Dlx3 deletion could directly affect the network of molecular switches and promote osteoblastic differentiation and bone-forming activity via an enhancement of the occupancy of bone-activator TFs such as Dlx5 and Runx2.…”
mentioning
confidence: 99%